Prosocial Behavior of Peer Support Groups in Overcoming Problems of People Living With HIV/AIDS in Malang Raya - Rinikso Kartono; Juli Astutik; Al Banda Arya Rekso Negoro (Universitas Muhammadiyah Malang, 2022)
The main problem that is always faced by people living with HIV/AIDS (PLWHA) is physical problems, and social problems in the form of stigma and discrimination, which causes PLWHA to lose social support from family and friends, be isolated, and hidden, and be powerless. This study aims to analyze the emergence of volunteers from Peer Support Groups (PSG) who help PLWHA a lot by providing social support in the form of love, educational information, care, instrumental support to spiritual support, in full without asking for compensation. This study uses a qualitative approach with a descriptive narrative type. This study found that prosocial behavior is formed by understanding the events of self and others who are infected with HIV. The existence of subjective understanding encourages various forms of social behavior of PSG members to be carried out voluntarily without compensation. Several forms of social behavior shown by PSG include; providing shelter, providing education, sacrificing time, energy, and money, providing counseling and motivation, patient care, corpse care, advocacy, and providing care for orphans of PLWHA. Several forms of social behavior shown by PSG include; providing shelter, providing education, sacrificing time, energy, and money, providing counseling and motivation, patient care, corpse care, advocacy, and providing care for orphans of PLWHA. Several forms of social behavior shown by PSG include; providing shelter, providing education, sacrificing time, energy, and money, providing counseling and motivation, patient care, corpse care, advocacy, and providing care for orphans of PLWHA.